The Effect of Immersion Concentration of Coconut Water and Dosage of NPK Fertilization on Growth and Yield of Peanut (Arachis hypogeae L.) - Okti, Reski Dwi; Setiyono, Setiyono; Sholikhah, Ummi; Purnamasari, Ika; Meliala, Susan Barbara Patricia Sembiring; Savitri, Dyah Ayu; Arum, Ayu Puspita (Green Engineering Society, 2024)
One problem of peanut cultivation is the inability of peanut seeds to be stored long-term. Prolonged storage of seed peanuts causes seed deterioration due to seeds losing reserves of food and nutrient that cause the seeds difficult to germinate. As well as other problems, namely Nitrogen, Phosphorus and Potassium fertilization which has not been based on plant needs, fertilizer application tends to be excessive. The purpose of this study is to know the interaction and the main effect of the concentration treatment of coconut water immersion and NPK fertilization doses. This study used a factorial randomized block design with three replications. The first factor was the immersion concentration of coconut water (A) which consisted of 3 levels, namely: 0% coconut water (A1), 15% coconut water (A2), and 30% coconut water (A3) and the second factor was the dose of NPK fertilization (B) consisting of 4 levels, namely: NPK 0 g/plot (B1), NPK 22.5 g/plot (150 kg/ha) (B2), 45 g/plot (300 kg/ha) (B3), and NPK 67.5 g/plot (450 kg/ha) (B4). The results showed that (1) there was a significant interaction only on the number of primary branches with the applied treatment, 15% coconut water immersion concentration and NPK fertilization dose of 22.5 grams/plot (A2B2) (7.7 branches). (2) Concentration immersion in coconut water significantly affected the percentage of pithy pods, the percentage of empty pods, and the weight of 100 seeds, with the best treatment being the concentration of 15% coconut water immersion (A2). (3) Dose of NPK fertilization factor had a significant effect on harvesting age, percentage of empty pods, wet pod weight and productivity with the best treatment of 67.5 gram/plot NPK fertilization (B4).